High-pressure intermittent pneumatic compression applied immediately after physical exercise effectively reduces fatigue and enhances performance: a preliminary study - Ahmad Assagaf Rahmat; Gadis Meinar Sari; Mohammad Fathul Qorib; Nura Maulida Isna; Oky Dwi Silviyanti; José Vicente García-Jiménez; Awang Firmansyah (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: The use of intermittent pneumatic compression (IPC) has gained popularity in the sports world as one of the appropriate recovery methods to improve athlete performance and accelerate recovery. However, the benefits of IPC as a recovery method are still very limited.